Undergraduate baccalaureate nursing students' self-reported confidence in learning about patient safety in the classroom and clinical settings: An annual cross-sectional study (2010-2013). - Lukewich, Julia; Edge, Dana S.; Tranmer, Joan; Raymond, June; Miron, Jennifer; Ginsburg, Liane; VanDenKerkhof, Elizabeth (International Journal of Nursing Studies, 2015)
Background: Given the increasing incidence of adverse events and medication errors in healthcare settings, a greater emphasis is being placed on the integration of patient safety competencies into health professional education. Nurses play an important role in preventing and minimizing harm in the healthcare setting. Although patient safety concepts are generally incorporated within many undergraduate nursing programs, the level of students' confidence in learning about patient safety remains unclear. Objectives: Self-reported patient safety competence has been operationalized as confidence in learning about various dimensions of patient safety. The present study explores nursing students' self-reported confidence in learning about patient safety during their undergraduate baccalaureate nursing program. Design: Cross-sectional study with a nested cohort component conducted annually from 2010 to 2013. Setting and participants: Participants were recruited from one Canadian university with a four-year baccalaureate of nursing science program. All students enrolled in the program were eligible to participate. Methods: The Health Professional Education in Patient Safety Survey was administered annually. The Health Professional Education in Patient Safety Survey captures how the six dimensions of the Canadian Patient Safety Institute Safety Competencies Framework and broader patient safety issues are addressed in health professional education, as well as respondents' self-reported comfort in speaking up about patient safety issues. Results: In general, nursing students were relatively confident in what they were learning about the clinical dimensions of patient safety, but they were less confident about the sociocultural aspects of patient safety. Confidence in what they were learning in the clinical setting about working in teams, managing adverse events and responding to adverse events declined in upper years. The majority of students did not feel comfortable speaking up about patient safety issues. The nested cohort analysis confirmed these findings. In particular, confidence in acquiring basic clinical skills, learning about adverse events, and managing safety risks improved between Year 1 and Year 2, and confidence in managing safety risks declined in upper years. Conclusions: These findings suggest nursing students are confident in what they are learning about clinical aspects of patient safety, however, their confidence in learning about sociocultural aspects declines as they are increasingly exposed to the clinical environment. This suggests a need to address the impact of the practice environment on nursing students' confidence in what they are learning about patient safety.